BIPOC Community Perspectives on Environmental Justice in Georgia - Stephanie Cho; LP Green; Marianne Chung; Julia Lee-Hong; Darlene Xiomara Rodriguez (Journal of Community Engagement and Scholarship)
For decades, the environmental and climate justice spaces have been predominantly spearheaded by white activists and institutions, even as Black, Brown, and immigrant communities experience the brunt of climate change’s impact. The resulting exclusion of Black, Indigenous, and other people of color’s (BIPOC) experiences, perspectives, and leadership from environmental policy and conservation work has created significant blind spots that further perpetuate inequality (Jones, 2020). In a moment of reckoning, the historically white-led environmental and climate justice movements have begun to acknowledge the exclusion of people of color and its detrimental effects on BIPOC peoples and the movement overall. In order to rectify this exclusion, communities of color must be centered in movement strategy going forward. Furthermore, before community advocacy organizations and community members can advocate for and enact policies and other political decisions on behalf of these communities, we must first ask them what environmental harm has looked like and what solutions they need as we look toward the future. Toward that end, Democracy Lab South and partners conducted the first and only multilingual statewide environmental justice survey of Georgia’s BIPOC and immigrant communities in 2022. This survey establishes a baseline understanding of these communities’ current perceptions, needs, practices, and potential localized solutions. It is our hope that the survey and resulting policy report will serve as a catalyst for building a robust statewide environmental movement that centers those most affected by climate and environmental issues.